Elections and (mis)reporting of COVID-19 mortality - Parrendah Adwoa Kpeli; Günther G. Schulze; Nikita Zakharov (University of Freiburg, Department of International Economic Policy (iep), 2024)
We investigate the effect of elections on underreporting COVID-19 mortality, measured as the difference between excess mortality and official statistics. Our identification strategy takes advantage of a natural experiment of the unanticipated onset of the Coronavirus pandemic in 2020 and the asymmetric electoral schedule of presidential elections around the world, in which some countriesfaced the pandemic with upcoming elections in the next two years, while others did not have this electoral pressure. Contrary to conventional wisdom that governments manipulate information downwards to enhance reelection probabilities, we find that democratic governments facing elections in the following years report COVID fatalities more truthfully. We explain the result by a potential aversion to the costs associated with exposed underreporting: using Gallup poll data for 2020 we show that underreporting of COVID-19 mortality potentially undermines trust in government but only in relatively democratic countries.
Keywords: D72; I18; P50; 330; COVID-19; data manipulation; elections; democracy